HOW DO WE KNOW WHETHER THERE HAS BEEN PROGRESS IN TEACHER AUTONOMY? - SPRENGER, Terezinha Maria (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
This paper presents a case study to illustrate how activity theory (Leontiev 1978; Engeström 1987, 1999) and the expansive learning framework (Engeström 1987, 1999) were used to evaluate the development of teacher autonomy in an online course on preparing EFL classroom materials. It is assumed that the learning by expansion model is similar to conscientização (Freire 1980, 1982), a key element in the development of teacher autonomy, according to the perspective in the study.